2017
DOI: 10.5330/1096-2409-21.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Mental Health Literacy through Bibliotherapy in School-Based Settings

Abstract: Considering that one in five children has or has had a mental disorder in a given year (National Institute of Mental Health, 2010), the demand for mental health services within the school setting is immense. Bibliotherapy can serve as a preventative and responsive treatment for increasing mental health literacy within the school setting. The authors review relevant bibliotherapy and mental health literacy research, introduce the concept of mental health literacy in the school setting, and provide counselors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Therefore, the need for resources such as children's literature addressing parental incarceration to support the emotional well‐being of affected children is urgent. Some children and adolescents have benefited from similar approaches when coping with death, bullying, depression, trauma and stress (Hazlett‐Stevens & Oren, 2017; Moulton et al, 2011; Mumbauer & Kelchner, 2017; Sunderland & McGlashan, 2012; Wiseman, 2013). Encountering characters in books who face similar challenges, such as a parent's incarceration, can help children share their own stories and manage their struggles through identification with the characters (Baghban, 2007; Catalano, 2017; De Vries et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the need for resources such as children's literature addressing parental incarceration to support the emotional well‐being of affected children is urgent. Some children and adolescents have benefited from similar approaches when coping with death, bullying, depression, trauma and stress (Hazlett‐Stevens & Oren, 2017; Moulton et al, 2011; Mumbauer & Kelchner, 2017; Sunderland & McGlashan, 2012; Wiseman, 2013). Encountering characters in books who face similar challenges, such as a parent's incarceration, can help children share their own stories and manage their struggles through identification with the characters (Baghban, 2007; Catalano, 2017; De Vries et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Bibliotherapy has been applied as an approach to educate children on their multicultural identity (Ford et al, 2000(Ford et al, , 2019, coping with trauma (De Vries et al, 2017), bullying (Flanagan et al, 2013), managing anxiety (Rapee et al, 2006), parental divorce (Aziz et al, 2018) and addressing parental incarceration (Clopton & East, 2008;Hames & Pedreira, 2003;Lopez & Bhat, 2007;Nguyen, 2022;Oslick, 2010Oslick, , 2012Oslick, , 2013Shlafer & Scrignoli, 2015;Warren et al, 2019). Moreover, children's literature has proven effective in helping children grapple with a myriad of challenges, including but not limited to death, bullying, depression, trauma and stress (Hazlett-Stevens & Oren, 2017;Moulton et al, 2011;Mumbauer & Kelchner, 2017;Sunderland & McGlashan, 2012;Wiseman, 2013).…”
Section: Broaching Sensitive Subject Matter With Childrenmentioning
confidence: 99%
“…These groups might be global or more specific to some of the significant proxy items in this study, such as students experiencing feelings of hopelessness, not straight students, nonbinary students, or students who experience bullying (or engage in bullying behaviors). Groups are another appropriate setting to implement mental health literacy and bibliotherapy techniques; research has shown their effectiveness in educating students, fostering connections, and providing structure in the group process (Mumbauer & Kelchner, 2017). School counselors can use this modality both to address suicidal ideation and to prevent suicide attempt.…”
Section: Discussionmentioning
confidence: 99%
“…School counselor instruction in eighth-grade classrooms can utilize social/emotional curriculums to support the school culture of acceptance and inclusion (and reduce bullying behaviors), and incorporate other practices like community circles and restorative justice. Classroom lessons are also ripe for introducing mental health literacy and bibliotherapy, with the capacity to “connect children with their peers, which is a significant predictor of students’ socioemotional well-being” (Mumbauer & Kelchner, 2017, p. 91). These practices also encourage and empower students about how and when to ask for help from trusted adults (such as school counselors), modeling and normalizing this skill if a student experiences suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…The main focus of mental healing with this method is to reduce emotional stress, psychological worries, and various kinds of psychological disorders (Mumbauer & Kelchner, 2017) . The bibliotherapy method has been shown to be effective in overcoming self-efficacy problems in parents of children with special needs (Öztemiz & Tekindal, 2021) and can even effectively contribute to changing students' self-concept for the better through counseling service interventions (Trihantoro et al, 2016) .…”
Section: Bibliotherapy As An Innovation In Spiritual Guidancementioning
confidence: 99%